Teaching Arabic Reading Skills For Bahtsul Masail Purpose In Islamic Boarding School/ تعليم مهارة القراءة لأغراض بحث المسائل في المعهد - Siti Jubaidah; Imam Asrori; Syuhadak Syuhadak (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
In teaching Arabic as a foreign language, several problems were found, including linguistic and non-linguistic issues. Salafiyah Shirothul Fuqoha Islamic Boarding School has a system to solve this problem so that students have high reading competence, namely a Teaching System of Reading Skills for Bahtsul Masail purpose. This study aims to describe and analyze: (1) the Teaching System of Reading Skills for Bahtsul Masail purpose at Salafiyah Shirothul Fuqoha Islamic Boarding School; (2) the contribution of Teaching System of Reading Skills for Bahtsul Masail purpose to increase student competence at Salafiyah Shirothul Fuqoha' Islamic Boarding School Malang. This study uses a qualitative approach with case studies. Observation, interviews, and documentation obtained data collection techniques in this study. According to Miles and Huberman, data analysis was carried out using data analysis techniques with three steps: data reduction, data display, and conclusions drawing. The results of this study are (1) Teaching System of Reading Skills for Bahtsul Masail purpose at the Salafiyah Shirothul Fuqoha Islamic Boarding School Malang consists of Regular program, Sorogan, Takhassus, Part Bahtsul Masail, and Joint Bahtsul Masail; (2) The contribution of the Teaching System of Reading Skills for Bahtsul Masail purpose can increase student competence to achieve creative reading competence.